Forecasting random walks under drift instability - Mohammad Hashem Pesaran; Andreas Pick (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper considers forecast averaging when the same model is used but estimation is carried out over different estimation windows. It develops theoretical results for random walks when their drift and/or volatility are subject to one or more structural breaks. It is shown that compared to using forecasts based on a single estimation window, averaging over estimation windows leads to a lower bias and to a lower root mean square forecast error for all but the smallest of breaks. Similar results are also obtained when observations are exponentially down-weighted, although in this case the performance of forecasts based on exponential down-weighting critically depends on the choice of the weighting coefficient. The forecasting techniques are applied to monthly inflation series of 21 OECD countries and it is found that average forecasting methods in general perform better than using forecasts based on a single estimation window.
Keywords: C22; C53; 330; forecast combinations; averaging over estimation windows; exponentially downweighting observations; structural breaks; Prognoseverfahren; Zeitreihenanalyse; Maßzahl; Random Walk; Volatilität; Strukturbruch; Theorie; Inflation; Prognose; Schätzung; OECD-Staaten